TRADISI PERANG API PADA MASYARAKAT BALI - I Nyoman Suka Ardiyasa; Putu Maria Ratih Anggraini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The fire worship tradition has long been practiced by the Balinese, which is manifested in various traditions and rituals in Bali. Balinese people believe that this nature consists of a scale environment (real) and a niskala environment (not real) which must always be kept in harmony. The tradition of worshiping Hyang Agni or Api is believed to be due to the influence of volcanoes or volcanoes that are still active in Bali, such as Mount Agung and Mount Batur, where volcanic activity is still going on. The history of the worship of Hyang Agni (God of Fire) has existed since the ancient Balinese era since the IX century AD. This can be seen from the findings of inscriptions that mention the worship of the God of Fire as in Sukawana AI (Caka 804 = 892M) and various living and ancient folklores. grow up in society. There are several traditions of the fire war in Bali that still exist today, including the fire war tradition in the Unggahan village of Buleleng Bali, the Siat Geni tradition in the Ngapat ceremony in the Tuban traditional village, Badung, the fire war in Jasri village, Karangasem district, the war tradition in Nagi village, Ubud. , Gianyar, Lukat Gni Tradition in Klungkung Regency. The whole tradition still exists today and continues to be implemented along with the times.Keyword : Fire War, Balinese Society